2019
DOI: 10.31246/mjn-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

Plain water and beverage consumption patterns among university students in Puncak Alam, Malaysia

Abstract: Introduction: Data on water and sugar sweetened beverages (SSB) intake among young adults in Malaysia is sparse. This study aimed at measuring the intake of plain water and SSB among undergraduate students in a Malaysian university and examine its association with body mass index (BMI). Methods: A total of 376 undergraduate students aged 18-30 years were recruited. A selfadministered questionnaire was used to determine the SSB consumption pattern. The questionnaire consisted of five sections that included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Tea and caffeinated drinks (25.5%) were the most consumed SSBs on a daily basis amongst the participants in the present study. This trend is similar to studies by Norimah et al [22] and Teng et al [15], which reported a high consumption of coffee and tea amongst their participants. These findings are in agreement with a study that demonstrated that the reasons behind the high consumption of coffee and tea amongst students included helping them to concentrate, keep them awake at night during exam preparation phases, and staying active during classes [23].…”
Section: The Association Between Kap On Ssb With Body Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tea and caffeinated drinks (25.5%) were the most consumed SSBs on a daily basis amongst the participants in the present study. This trend is similar to studies by Norimah et al [22] and Teng et al [15], which reported a high consumption of coffee and tea amongst their participants. These findings are in agreement with a study that demonstrated that the reasons behind the high consumption of coffee and tea amongst students included helping them to concentrate, keep them awake at night during exam preparation phases, and staying active during classes [23].…”
Section: The Association Between Kap On Ssb With Body Compositionsupporting
confidence: 92%
“…The adopted BEVQ investigates the frequency of plain water (bottled water/tap water) and SSB intake on a weekly basis [15]. It consists of 10 types of beverages, including plain water, 100% fruit juice, sweetened fruit beverages, full-cream milk, low-fat milk, skimmed milk, regular soft drinks, energy and sports drinks, and alcoholic drinks.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that college students tended to choose their drinking beverages on the basis of their cost, as well as taste factors, rather than the nutritional information associated with a particular drink, which suggests that college students may be particularly at risk due to their lack of sufficient water intake, as well as a lack of understanding regarding the need to adhere to guidelines related to daily water intake [63,64]. A high rate was identified by Teng et al [65], who showed that plain water was the most consumed beverage (92.30% of the participants).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a conscious effort to limit their SSB intake and make healthier choices, such as opting for beverages without added sugars (9,21). This aligns with the recommendations of health authorities advocating for a reduction in SSB intake (9,22). The positive attitudes towards reducing SSB consumption may indicate a willingness to adopt healthier behaviors, which can be further encouraged through targeted interventions aimed at improving knowledge about SSBs.…”
Section: Discussionmentioning
confidence: 56%